Fibre-Plastic Composites: Oil Palm Frond and Rubberwood Fibres Blended with Polypropylene - Liew, Kang Chiang (1998)
Natural lignocellulosic fibres have become more important nowadays because "new" types of composite material can be produced from them. The objectives of this study are to evaluate the suitability of producing fibrepolypropylene composite using oil palm frond fibre and rubberwood fibre. The effects of different fibre size and fibre content on the physical and mechanical properties of the composite produced are assessed to give an insight into fibrematrix adhesion and fibre damages. In this study, crude fibres of oil palm fronds were atmospherically refined into fine fibres whilst rubberwood fibres were obtained from a local fibreboard plant. These fibres were later screened into different sizes: < 0.5 mm, 0.5 - 1 mm, 1 - 2 mm and > 2 mm. The screened fibres were melt-blended with polypropylene at different ratios in a Brabender Plasti-Corder equipped with a mixer of type W 350 E - 2 Heating Zones. The mixing condition was set at a rotor speed of 30 rpm at 180°C for 30 minutes. Moulded composites were prepared for evaluation of tensile, flexural, IZOD impact resistance - notched and ROCKWELL hardness according to ASTM standards.